Pola dan Iklim Komunikasi Suami Istri, serta Pengasuhan Anak Cerebral Palsy - Lasmi Purnawati; Sarwititi Sarwoprasodjo; Herien Puspitawati (Jurnal Komunikasi Pembangunan, 2017)
Communication pattern in marriage has a specific relation to parenting a child with cerebral palsy. It determine their ability to deal with parenting and developing a child. This research is aimed to analyze a link between communication pattern in marriage, communication climate and parenting a child with cerebral palsy. It was done to use quantitative method with the survey that was focusing on an individual spouse that has a child with cerebral palsy. The research found that communication pattern tends a positive simetric type in parenting a child with cerebral palsy. Then, communication climate of spouse that has a child with cerebral palsy is a defensive and supportive. Parenting a child with cerebral palsy that was being found is acceptance.